(untitled) (American Journal of Islam and Society, 2006)
On 22-24 February 2006, the Asia-Pacific Center for Security Studies (APCSS) held this conference on the complex security environment of Central Asia as the region continues to struggle with the phenomena of terrorism and religious extremism, poverty and corruption, political instability and authoritarian governance, as well as great power (China, Russia, and the United States) suspicion and rivalry. These challenges are not uniquely Central Asian, but the region seems to be particularly vulnerable to them as its young nations are undergoing a significant political, social, and economic transformation. How the region copes with these issues will extend important lessons to the world as a whole. This forum examined the trilemma posed for Central Asia and the broader Asia-Pacific region. First, for the war on terror in the region to be successful, it must evolve into well-implemented stabilization and reconstruction efforts as well as dramatic improvements in governance and human rights. Second, no country on its own can alter the situation in Central Asia, for such an effort requires cooperation between all of the major powers and stakeholders in the region (India, Iran, Pakistan, and Turkey). The magnitude of the problem of terrorism, which affects most if not all countries in the region, should preclude another variation of the Great Game. Finally, while the number of regional organizations and security forums in Central Asia has been growing, the low degree of coordination among them triggers counterproductive rivalries and plays into the hands of extremist elements. Since terror knows no borders, what happens in Central Asia significantly impacts developments elsewhere. Although the counterterrorist effort in Central Asia has successfully marginalized the Taliban and al-Qaeda, the localization of the terrorist threat means that new autonomous extremist cells continue to emerge in Central Asia. The sources of proliferation of radical Islam can be found in socioeconomic deprivation, widespread corruption, and political ...